Pregunta
Suppose that the functions \( f \) and \( g \) are defined for all real numbers \( x \) as follows, \[ \begin{array}{l}f(x)=3 x \\ g(x)=4 x^{2} \\ \text { Write the expressions for }(g-f)(x) \text { and }(g \cdot f)(x) \text { and evaluate }(g+f)(2) \\ (g \cdot f)(x)=\square \\ (g+f)(2)=\square\end{array} \]
Ask by Gross Johnston. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\[
(g \cdot f)(x) = 12x^3
\]
\[
(g + f)(2) = 22
\]
Solución
Let's work through each part of the problem step by step.
### Given Functions:
- \( f(x) = 3x \)
- \( g(x) = 4x^2 \)
### 1. **Expression for \((g \cdot f)(x)\):**
The product \((g \cdot f)(x)\) is found by multiplying the two functions together:
\[
(g \cdot f)(x) = g(x) \times f(x) = 4x^2 \times 3x = 12x^3
\]
**So,**
\[
(g \cdot f)(x) = 12x^3
\]
### 2. **Evaluation of \((g + f)(2)\):**
First, find \((g + f)(x)\), then substitute \( x = 2 \):
\[
(g + f)(x) = g(x) + f(x) = 4x^2 + 3x
\]
Now, evaluate at \( x = 2 \):
\[
(g + f)(2) = 4(2)^2 + 3(2) = 4 \times 4 + 6 = 16 + 6 = 22
\]
**So,**
\[
(g + f)(2) = 22
\]
### **Final Answers:**
\[
(g \cdot f)(x) = 12x^3
\]
\[
(g + f)(2) = 22
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To find the expressions for \((g-f)(x)\) and \((g \cdot f)(x)\), we first calculate \(g(x) - f(x)\) and \(g(x) \cdot f(x)\): 1. \((g-f)(x) = g(x) - f(x) = 4x^2 - 3x\) 2. \((g \cdot f)(x) = g(x) \cdot f(x) = (4x^2)(3x) = 12x^3\) Now, to evaluate \((g+f)(2)\): \[ (g+f)(x) = g(x) + f(x) = 4x^2 + 3x \] Calculating this at \(x=2\): \[ (g+f)(2) = 4(2)^2 + 3(2) = 4(4) + 6 = 16 + 6 = 22 \] Thus, we have: \[(g \cdot f)(x) = 12x^3\] \[(g + f)(2) = 22\]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium